Event Management and Sustainability - Raj, Razaq (CABI, 2014)
The book then gives a full and complete view of the concepts of sustainable management and how it relates to various sectors within the events industry. It illustrates the fundamental importance of local communities, businesses and interested stakeholders in relation to future events in regional, national and international locations. Historical and documented reports supplement this area. Next the book focuses on international governing bodies and national government strategic objectives as the cornerstone for sustainable development in the events sector. The relationship between these strategic objectives and on-the-ground operational responsibilities is presented using research by contributing authors and accredited organizations to add scope and depth to the publication. The book is not intended to become a reference material for practitioners or appointed advocates. However, best practice case studies are presented within the book to highlight and explain particular sustainable management issues where necessary. The book is intended to support practitioners in their operational and administrative duties and to educate undergraduates/ postgraduates within their industry sectors throughout the UK and on an international basis.